2020
DOI: 10.48208/headachemed.2020.supplement.63
|View full text |Cite
|
Sign up to set email alerts
|

Uso de cafeína em pacientes com cefaleia: uma revisão sistemática

Abstract: IntroduçãoAproximadamente 11% dos adultos em todo o mundo têm enxaqueca, um distúrbio neurológico crônico caracterizado por ataques episódicos de dor de cabeça acompanhados por sintomas autonômicos, bem como sensibilidade à luz e sons. A enxaqueca difere da cefaleia do tipo tensional (CTT), uma condição mais comum que se caracteriza por cefaleia leve a moderada com poucos ou nenhum sintoma associado. Os medicamentos para dor de cabeça com cafeína, isoladamente ou em combinação com outros tratamentos, são ampla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, Hershkovitz [6], based on morphological data, recognized only two species of cuxiu, C. albinasus and C. satanas, with the latter species being divided into three subspecies: C. s. satanas, C. s. chiropotes and C. s. utahicki. Silva Júnior and Figueiredo [7], based on a fragment of cytochrome b, suggested that the subspecies C. s. satanas and C. s. utahicki should be raised to species status. Additionally, they also proposed that populations from opposite banks of the Branco River were distinct species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Hershkovitz [6], based on morphological data, recognized only two species of cuxiu, C. albinasus and C. satanas, with the latter species being divided into three subspecies: C. s. satanas, C. s. chiropotes and C. s. utahicki. Silva Júnior and Figueiredo [7], based on a fragment of cytochrome b, suggested that the subspecies C. s. satanas and C. s. utahicki should be raised to species status. Additionally, they also proposed that populations from opposite banks of the Branco River were distinct species.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, C. chiropotes and Chiropotes sagulatus (Traill, 1821) are proposed to designate the taxa that inhabit the west and east banks of the Branco River, respectively. Accordingly, this classification with five species of Chiropotes (C. chiropotes, C. albinasus, C. sagulatus, C. satanas and C. utahicki) was followed in the present study [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation